(untitled) (Research, Society and Development, 2024)
This study aims to understand the complex relationship between intestinal microbiota and mental health, exploring the mechanism by which this interaction may occur, the major neuropsychological disorders involved, and potential therapeutic implications. Methodologically, a comprehensive literature review was conducted, focusing on studies from the past 20 years obtained from the National Library of Medicine database (PubMed). The results and discussion section revealed significant correlations between intestinal microbiota and various mental health disorders, including anxiety, depression, stress, schizophrenia, and psychosis. The gut-brain axis emerged as a crucial mediator, influencing neurotransmitter production, immune responses, and emotional behaviors. Probiotic supplementation and dietary interventions have shown promise as complementary therapeutic approaches, potentially alleviating symptoms associated with mental health conditions. In conclusion, this review highlights the complex interplay between intestinal microbiota and mental well-being, underscoring the need for further research to elucidate underlying mechanisms and translate findings into clinical practice. By advancing our understanding of this relationship, we can pave the way for comprehensive approaches to mental health care, shaping the future of medicine.